HDL cholesterol: reappraisal of its clinical relevance - März, Winfried; Kleber, Marcus E. (Clinical research in cardiology, 2017)
Background: While several lines of evidence prove that elevated concentrations of low-density lipoproteins (LDL) causally contribute to the development of atherosclerosis and its clinical consequences, high-density lipoproteins are still widely believed to exert atheroprotective effects. Hence, HDL cholesterol (HDL-C) is in general still considered as “good cholesterol”. Recent research, however, suggests that this might not always be the case and that a fundamental reassessment of the clinical significance of HDL-C is warranted.Method: This review article is based on a selective literature review.ResultsIn individuals without a history of cardiovascular events, low concentrations of HDL-C are inversely associated with the risk of future cardiovascular events. This relationship may, however, not apply to patients with metabolic disorders or manifest cardiovascular disease. The classical function of HDL is to mobilise cholesterol from extrahepatic tissues for delivery to the liver for excretion. These roles in cholesterol metabolism as well as many other biological functions of HDL particles are dependent on the number as well as protein and lipid composition of HDL particles. They are poorly reflected by the HDL-C concentration. HDL can even exert negative vascular effects, if its composition is pathologically altered. High serum HDL-C is therefore no longer regarded protective. In line with this, recent pharmacological approaches to raise HDL-C concentration have not been able to show reductions of cardiovascular outcomes.Conclusion: In contrast to LDL cholesterol (LDL-C), HDL-C correlates with cardiovascular risk only in healthy individuals. The calculation of the ratio of LDL-C to HDL-C is not useful for all patients. Low HDL-C should prompt examination of additional metabolic and inflammatory pathologies. An increase in HDL-C through lifestyle change (smoking cessation, physical exercise) has positive effects and is recommended. However, HDL-C is currently not a valid target for drug therapy.